Probiotics and Bone Health: It takes GUTS to Improve Bone Density - Rupesh K Srivastava; Hamid Yousf; Geetanjali B Tomar (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2015)
Probiotics are a class of symbiotic bacteria whose administration in adequate amount provides health benefits to the host by altering the composition of gut microbiota. The gut microbiota is known to regulate both the host immune system and metabolism, leading to increased bone mass by inhibiting bone resorption. Ovariectomy induced estrogen deficiency which mimics postmenopausal osteoporosis in women leads to enhanced bone inflammation and resorption. Recently it has been reported that different strains of bacteria (e.g. Lactobacillus, Bifidobacteria etc.), have important role in gut-bone regulation in ovariectomized mouse. Thus administration of probiotics can open up new avenues in treatment of various inflammatory bone conditions such as osteoporosis and rheumatoid arthritis by modulating the delicate balance between the gut microbiota and immune system.